The Influence of Transfer Pricing, Corporate Governance, CSR, and Earnings Management on Tax Aggressiveness - Robin, Robin; Toni, Nagian; Noviyanti Simorangkir, Enda (AGUSPATI Research Institute, 2021)
This study aims to test and analyze tax aggressiveness in various industrial sector Indonesia Stock Exchange manufacturing companies (IDX). The variables tested include Transfer Pricing, Corporate Governance, Corporate Social Responsibility, Earnings Management and Tax Aggressiveness. This research involves various industrial sector Indonesia Stock Exchange manufacturing companies (IDX) in 2017-2019. Sample selection was done by using the purposive sampling method. The data used is external data, which is obtained by accessing IDX website. The data analysis process is carried out by calculating the PLS Algorithm using SmartPLS and then testing the hypothesis. The results show that Corporate Governance and Earnings Management have effect with positive relation direction on Tax Aggressiveness, Transfer Pricing and Corporate Social Responsibility have no effect on Tax Aggressiveness, Transfer Pricing has an effect with positive relation direction to Earnings Management, Corporate Governance and Corporate Social Responsibility have no effect on Earnings Management.